HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP DENGAN KEJADIAN OBESITAS PADA PEGAWAI SEKRETARIAT DAERAH PROVINSI RIAU - Septy Dwi Indriani; Fifia Chandra Chandra; Huriatul Masdar (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Obesity is an increase body weight above normal caused by multifactorial such as genetic factor, individual factors and especially the sedentary lifestyle. Worker community are recognized as one of community at high risk of obesity and the risk can be minimalized by having good knowledge and attitude of obesity and its prevention. The aim of this research was to know the relationship of knowledge and attitude with obesity at the Local Secretary Officer Riau Province. A cross sectional research was performed involving 44 subjects. Obesity was determined by using body mass index. Knowledge and attitude were measured by some questionnaire. The result of obesity showed 50% samples were obese. The result of knowledge showed 36.4% subject had good knowledge, 56,8% had enough knowledge and 6.8% subject had bad knowledge. Futhermore, the result of attitude showed 11.4% subjects had good attitude, 75% subjects had enough attitude and 13.6% subjects have a bad attitude. Statistic analyzing using Kolmogorov Smirnov test showed there was no relationship either between knowledge and obesity or attitude and obesity (p> 0,05) in this research.Keywords: knowledge, attitude, obesity